Compositional analysis of coffee containing javamide I/II and investigation of health effects in rats fed a high fat diet - Jae B. Park; Renee Peters (Scientific Reports)
Abstract Coffee containing javamide I/II (CCJ12) is commonly found in the market. However, no information is available about chemical composition of CCJ12 and in vivo effects on obesity. Therefore, in this paper, the composition of CCJ12 was analyzed by HPLC and LC/MS, and effects on bodyweight, metabolic (HDL, LDL, TG, leptin, adiponectin), cardiovascular risk (sE-selectin, C-reactive protein,), and inflammatory (MCP-1, TNF-alpha) factors were investigated in a rodent model. In CCJ12, > 700 compounds were identified by LC/MS and the amounts of javamide I/II, caffeine and chlorogenic acids were quantified by HPLC. For the animal study, rats were placed into three groups (each n = 10); (CG group (a control diet with water), FG group (a high fat diet with water), and FCG group (a high fat diet with CCJ12)) and the study was conducted for 20 weeks. The data showed no significant differences in water/food intakes between all three groups. However, the FG and FCG groups showed weight gain, in comparison to the CG group (P < 0.05). Also, the FG and FCG groups showed higher levels of LDL, TG, and leptin than the CG group (P < 0.05). However, no significant differences were found in bodyweight, HDL, LDL, TG, leptin, and adiponectin levels between the FG and FCG groups. Also, no significant differences were noted in sE-selectin, C-reactive protein, and MCP-1 levels between the FG and FCG groups. However, TNF-alpha level was found to be down in the FCG group, in comparison to the FG group (P < 0.05). Our study suggests that CCJ12 may have no adverse effects on bodyweight, HDL, LDL, TG, adiponectin, leptin, sE-selectin, C-reactive protein, and MCP-1, but may have a beneficial effect on TNF-alpha in rats fed a high fat diet.